Methotrexate Hepatotoxicity in Psoriatics: Report of 104 Patients from Nova Scotia, with Analysis of Risks from Obesity, Diabetes and Alcohol Consumption During Long Term Follow-Up - DA Malatjalian; JB Ross; CN Williams; SJ Colwell; BJ Eastwood (Canadian Journal of Gastroenterology)
BACKGROUND AND DESIGN: Methotrexate (MTX) hepatotoxicity in psoriatic patients is well recognized, but there are discrepancies in the reported incidence and associated risk factors. This retrospective study describes 104 Nova Scotian patients with psoriasis seen between 1979 and 1990. Patients received MTX over one to 11 years (mean 3.38), with baseline and annual follow-up liver biopsies. Clinical data were obtained by chart review. Statistical analysis evaluated the risks associated with obesity, diabetes, alcohol consumption and duration of therapy, with the histological grade of liver biopsies.